Evolution of territoriality in Hylinae treefrogs: Ecological and morphological correlates and lineage diversification - Luría-Manzano, Ricardo; Pinheiro, Paulo D. P.; Kohlsdorf, Tiana; Haddad, Célio F. B. [UNESP]; Martins, Marcio (Oxford University Press (OUP), 2023)
Given the diverse nature of traits involved in territorial defence, they may respond to different selective pressures and then exhibit distinct patterns of evolution. These selective pressures also may cause territorial behaviour to be associated with environmental and morphological variables. Such associations, however, have mostly been studied at the intraspecific level, being phylogenetic analyses of territoriality in a broad taxonomic framework rare in the literature. We used the anuran subfamily Hylinae to test (1) whether two territorial-behaviour traits with different levels of aggression—territorial call and physical combat—are evolutionarily more labile than a morphological trait used in physical combat—the spine-shaped prepollex; (2) whether reproduction in lentic waters and phytotelmata, as well as resource scarcity, might favour the occurrence of territoriality; (3) if physical combat is more important than territorial call for the evolution of body size and sexual size dimorphism and (4) the relationships between territorial-behaviour traits and lineage diversification. We mainly used the literature to build two datasets with different levels of certainty. Territorial-behaviour traits exhibited intermediate levels of phylogenetic signal in Hylinae, whereas the phylogenetic signal for the presence of the spine-shaped prepollex was strong. We found support for the hypothesis that reproduction in lentic water favours the occurrence of territorial behaviour, because the expression of territorial-behaviour traits was more associated with reproduction in lentic than in lotic waters. Territorial-behaviour traits were not correlated with annual precipitation nor with habitat complexity. Body size and sexual size dimorphism were not correlated with the presence of territorial call nor with physical combat. We identified negative correlations between diversification rates and physical combat. Relationships of territorial call and physical combat with diversification rates suggest that these territorial behaviours influence evolutionary processes in different ways.
Keywords: aggression; diversification rates; phylogenetic signal; physical combat; territorial call